2010
DOI: 10.1007/s10453-009-9153-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends in grass pollen season in southern Spain

Abstract: The main characteristics of Poaceae pollen season at 8 sites in Andalusia were studied. Special attention was paid in the trends of grass pollen-season start and peak dates. Moreover, we analyse the intensity of the grass pollen season over the study period as well as potential temporal and spatial patterns in these data. Statistical analysis was performed to determine the possible influence of weather-related parameters on variations in the grass pollen season. Main results show an advance in the start and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 23 publications
2
25
2
3
Order By: Relevance
“…2) is in accordance with the reports from other regions [21,22], but contrary to other studies [5,23]. Poaceae pollen was observed during all the year, especially in spring when most grass species bloom [24].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…2) is in accordance with the reports from other regions [21,22], but contrary to other studies [5,23]. Poaceae pollen was observed during all the year, especially in spring when most grass species bloom [24].…”
Section: Discussioncontrasting
confidence: 55%
“…Grasses are both annual and perennial herbs, and most species are anemophilous [2], producing large amounts of pollen grains during a short period of time [3]. From the clinical point of view, their pollen is considered one of the most important aeroallergens in Europe [4,5] and a major cause of pollinosis in several parts of the world [6][7][8]. In Portugal, Poaceae pollen is one of the most frequent aeroallergens and the main cause of pollinosis in the sensitized population [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…If so, this must be particularly important in unpredictable environments e as South-eastern Spain e where the length of the rainy season and quantity of rain could vary drastically from year-to-year, besides causing confusion in the flowering patterns. Other aerobiological studies also point out that flower phenology in grass species varies year-to-year (Emberlin et al, 1994;Fernández-González et al, 1999;García-Mozo et al, 2009, 2010, supporting the idea that water availability is one of the most important factors for the onset of flowering.…”
Section: Pulse Dynamics In Annual Plantsmentioning
confidence: 88%
“…According to the data of the Counselling for Environment, Seville is the city of Andalusia with the highest number of days with an unacceptable air quality, being CO 2 one of the measured parameters (http://www.juntadeandalucia.es/ medioambiente/site/portalweb/). It has been demonstrated that high CO2 concentrations increase the plant growing (Poorter 1993) as well as the pollen production (Rogers et al 2006;García-Mozo et al 2010). Temperature, CO 2 concentration and many areas of wasteland on which grass grows could generate a longer pollen season in Seville.…”
Section: Discussionmentioning
confidence: 99%